2010
DOI: 10.1142/s0218216510008224
|View full text |Cite
|
Sign up to set email alerts
|

On an Inequality Between Unknotting Number and Crossing Number of Links

Abstract: It is well-known that for any link L, twice the unknotting number of L is less than or equal to the crossing number of L. Taniyama characterized the links which satisfy the equality. We characterize the links where twice the unknotting number is equal to the crossing number minus one. As a corollary, we show that for any link L with twice the unknotting number of L is greater than or equal to the crossing number of L minus two, every minimal diagram of L realizes the unknotting number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Hanaki and Kanadome characterized the link diagrams D which satisfy u(D) = (c(D) − 1)/2 as follows [4]: Let D be a knot diagram with u(D) = (c(D) − 2)/2. They showed in [1] that for any crossing point p of D, one of the components of D p is a reduced alternating diagram of a (2, p)-torus knot and the other component of D p has no self-crossings, where D p is the diagram obtained from D by smoothing at p. In addition, they showed that any minimal crossing diagram D of a knot K with u(K) = (c(K) − 2)/2 satisfies the above condition.…”
Section: Further the Equality Holds If And Only If Under-crossings Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Hanaki and Kanadome characterized the link diagrams D which satisfy u(D) = (c(D) − 1)/2 as follows [4]: Let D be a knot diagram with u(D) = (c(D) − 2)/2. They showed in [1] that for any crossing point p of D, one of the components of D p is a reduced alternating diagram of a (2, p)-torus knot and the other component of D p has no self-crossings, where D p is the diagram obtained from D by smoothing at p. In addition, they showed that any minimal crossing diagram D of a knot K with u(K) = (c(K) − 2)/2 satisfies the above condition.…”
Section: Further the Equality Holds If And Only If Under-crossings Ofmentioning
confidence: 99%
“…We give an example of Lemma 3.3. The equality holds if and only if D has property C. 4 The linking warping degree and linking number…”
Section: The Warping Degree Of An Oriented Link Diagrammentioning
confidence: 99%
See 1 more Smart Citation